Ordinary genius : the story of Albert Einstein - McPherson, Stephanie Sammartino (Minneapolis : Carolrhoda Books, 1995)
Recounts the life of the scientist whose theories of relativity revolutionized the way we look at space and time.
Different from the start -- On his own -- Secrets of the universe -- Einstein's happiest thought -- Proof from the sky -- Most famous scientist -- World travels -- Threatening shadow -- Atomic age.
Includes bibliographical references (pages 92-93) and index.
Middle School.
880
Accelerated Reader
Reading Counts!
109920
Keywords: Einstein, Albert, -- 1879-1955.; Physicists -- Biography -- Juvenile literature; Children's nonfiction; Biographies; Juvenile works